Comparison of the Molding Parameters Effects on Metal Injection Molded Specimens in the Real Experimental and Simulation Environments - Ledniczky, Gyorgy; Weltsch, Zoltan (Communications - Scientific Letters of the University of Zilina, 2024)
This article presents a technology that is not widely known. Previous research has investigated the effect of metal injection molding parameters on product shrinkage. The technology is mostly limited by the variations caused by deformation, so it is of paramount importance to focus on shrinkage. Consequently, within this study the injection molding simulations with 17-4PH type material was performed and its results were compared to the previously determined curve characters. The results obtained allow conclusions to be drawn regarding the accuracy of the simulation. Changing the parameters of the injection molding process can significantly affect the shrinkage factor. Changes in mold temperature, melt temperature and holding pressure affect the product dimensions. These parameters are also modified in the simulation setup and compared to the previous real measurements.
Keywords: metal injection molding; simulation; molding